A functional genetic screen for metabolic proteins unveils GART and the de novo purine biosynthetic pathway as novel targets for the treatment of luminal A ERα expressing primary and metastatic invasive ductal carcinoma - Cipolletti, Manuela; Leone, Stefano; Bartoloni, Stefania; Acconcia, Filippo (Frontiers in Endocrinology, 2023)
Targeting tumor cell metabolism is a new frontier in cancer management. Thus, metabolic pathway inhibitors could be used as anti-estrogen receptor α (ERα) breast cancer (BC) drugs. Here, the interplay among metabolic enzyme(s), the ERα levels and cell proliferation was studied. siRNA-based screen directed against different metabolic proteins in MCF10a, MCF-7 and MCF-7 cells genetically resistant to endocrine therapy (ET) drugs and metabolomic analyses in numerous BC cell lines unveil that the inhibition of GART, a key enzyme in the purine de novo biosynthetic pathway, induces ERα degradation and prevent BC cell proliferation. We report here that a reduced GART expression correlates with a longer relapse-free-survival (RFS) in women with ERα-positive BCs. ERα-expressing luminal A invasive ductal carcinomas (IDCs) are sensitive to GART inhibition and GART expression is increased in receptor-positive IDCs of high grade and stage and plays a role in the development of ET resistance. Accordingly, GART inhibition reduces ERα stability and cell proliferation in IDC luminal A cells where it deregulates 17β-estradiol (E2):ERα signaling to cell proliferation. Moreover, the GART inhibitor lometrexol (LMX) and drugs approved for clinical treatment of primary and metastatic BC (4OH-tamoxifen and the CDK4/CDK6 inhibitors) exert synergic antiproliferative effects in BC cells. In conclusion, GART inhibition by LMX or other inhibitors of the de novo purine biosynthetic pathway could be a novel effective strategy for the treatment of primary and metastatic BCs.